Multiple Positive Solutions of Semilinear Elliptic Problems in Exterior Domains. (12th December 2010) - Hsu, Tsing-San; Lin, Huei-Li
Abstract : Assume thatq is a positive continuous function inℝ N and satisfies the suitable conditions. We prove that the Dirichlet problem− Δ u + u = q ( z ) | u | p − 2 u admits at least three positive solutions in an exterior domain.